The Potential of Wind Energy as an Alternative Source in Turkey - Ilkilic, C.; Nursoy, M. (Taylor & Francis Inc, 2010)
Development in wind energy systems and the potential of wind energy in Turkey were studied; the wind energy potential of various regions was investigated in this study. A power equation was derived by a mathematical approach using the characteristics of wind energy, including rotor diameter, wind speed, and density of the wind power. The maximum power obtainable at each location with the wind speed of the location and the diameter of the rotor used has been calculated with this power equation. Nurdagi, Karabiga, Datca, Bandirma, Antakya, Mardin, and Kumkoy areas were found to be the most suitable areas for wind energy systems by their wind densities; Sinop, Gokceada, and Siverek are following these areas.
Keywords: renewable energy sources; wind energy; wind power